A high-accuracy non-contact online measurement method of the rotor-stator axial gap based on the microwave heterodyne structure. (March 2021) - Niu, Guangyue; Duan, Fajie; Liu, Zhibo; Jiang, Jiajia; Fu, Xiao
Highlights: A rotor-stator axial gap measurement method of microwave heterodyne is proposed. A signal carrier frequency error processing method is proposed. A phase measurement error processing method of distance scanning is proposed. The prototype's performance tests and evaluations are completed. Abstract: Rotor-stator axial gap is a key design parameter that affects the efficiency and safety of large rotating machines. An optimal axial gap value should be determined so that the rotating machines could work at the highest efficiency. To realize active clearance control (ACC) of rotating machines, high-accuracy non-contact online measurement of the axial gap must be carried out. However, direct current (DC) offset signals in absolute distance measurement, limited working space of sensors, and extremely harsh working environment all pose challenges to the realization of high-accuracy, non-contact, and online performance required by the axial gap measurement. Therefore, no mature measurement method exists at present. In this paper a rotor-stator axial gap measurement method was proposed based on the phase difference ranging principle. The structure of microwave heterodyne could effectively eliminate the errors caused by DC noise during absolute distance measurement. To break through the bottleneck of axial gap measurement accuracy, an axial gap measurement error model was established, and a signal carrier frequency error processing method along with a phase measurement error processing method based on spatial distance scanning were proposed. A platform modeled on the rotating machines' structure of edge labyrinth gas seal was built in the laboratory to carry out room temperature rotor-stator axial gap measurement. A prototype of the axial gap measurement based on a microstrip type sensor was developed, and the system's calibration and measurement performance evaluation experiments were carried out. Experimental results verified the effectiveness and accuracy of the proposed method. The measurement accuracy is better than 30 μm (at 0.5–3 mm) and better than 1% (at 3–18.5 mm).